The Effects of Liquidity, Audit Tenure, and KAP Reputation on Going Concern Audit Opinion - Mawaddah, Mawaddah; Rahayu, Sri; Yetti, Susfa (Journal of Business Management and Economic Development, 2023)
This study aims to find out how Liquidity, Audit Tenure, and KAP Reputation can affect acceptance of Going Concern Audit Opinions (Empirical Studies on Hotels, Resorts, and Cruise Lines Sub-Industry Companies listed on the IDX for the 2018-2021 period). The sample in this study is hotels, resorts, and cruise lines sub-industry companies using purposive sampling techniques so that 15 companies with 4 years of observation (60 observational data) were obtained that met the criteria. The data used is in the form of secondary data obtained from the company's annual report via the Indonesian Stock Exchange (IDX) website or the official website of the related company. Researchers use a quantitative approach to describe research problems through trend descriptions or being able to explain the relationship between variables. The analysis technique used in this study is data analysis using descriptive statistical analysis and logistic regression analysis with the help of SPSS 29 software. The data collection method is using documentation and literature study. The results of the study concluded that liquidity can significantly influence the acceptance of going concern audit opinions, while audit tenure and KAP reputation do not significantly the influence acceptance of going concern audit opinions.